A review on the formulation and analysis of anti-diabetic agent: Gliclazide - Helaluddin , Abul Bashar Mohammed; Alaama, Mohammed; Abdualkader, Abdualrahman Mohammed; Awang, Mohamed; Ahmed, Qamar Uddin; Abbas, Syed Atif (Trans Tech Publications, Switzerland, 2013)
Gliclazide is a second generation sulfonylurea, which is used as antidiabetics drug. It is orally administrated and used for the treatment of non-insulin-dependent diabetes mellitus (NIDDM) and has duration of action of 12 h or more. Beside its hypoglycaemic effects, gliclazide was reported to have many other important effects, such as: suppression of platelet functions, antithrombotic actions, decreased the production of tumour necrosis factor (TNF) á by endothelial cells and other effects. The unique activities of gliclazide has open a new avenue for the drug development research. This work is aimed to provide comprehensive information about gliclazide and its current research activities.